Ni-CoO / SiO2 aerogel as well as preparation method and application thereof

By using Ni-CoO/SiO2 aerogel catalyst, guaiacin is efficiently converted to phenol under photothermal conditions, solving the problem of low photothermal conversion efficiency in traditional technology, and achieving efficient and selective catalytic effect.

CN119524855APending Publication Date: 2025-02-28SHENYANG AEROSPACE UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411687183.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently convert guaiacin photothermal to phenol, and traditional photocatalytic materials have low utilization of solar energy, and have failed to fully utilize near-infrared light, and the photocatalytic performance is limited by the disadvantages such as photogenerating hole-electron pairs being easy to recombinate.

Method used

Ni-CoO/SiO2 aerogel was used as a catalyst to prepare SiO2 aerogel containing NiO and CoO by sol-gel method, and Ni-CoO/SiO2 aerogel was prepared by hydrogen reduction treatment. This catalyst can effectively promote the hydrodeoxygenation and deoxygenation process of guaiacin under photothermal conditions, and use the porous structure of SiO2 aerogel to provide a high temperature environment.

Benefits of technology

The efficient conversion of guaiacol into phenol under mild reaction conditions is achieved, the photothermal catalytic performance is improved, the high temperature can be achieved in inconcentrated sunlight, and the active components in the catalyst are highly dispersed, and the excellent photothermal catalytic performance is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524855A_ABST
    Figure CN119524855A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and provides Ni-CoO / SiO2 aerogel as well as a preparation method and application thereof. The method comprises the following steps: mixing water, tetraethoxysilane, ethanol and a hydrochloric acid solution, and hydrolyzing to obtain silica sol; the preparation method comprises the following steps: mixing silica sol, a nickel salt solution, a cobalt salt solution and a hydrochloric acid solution, and sequentially carrying out ultrasonic treatment, water bath and freeze drying to obtain SiO2 aerogel containing NiO and CoO; the preparation method comprises the following steps: in a reducing atmosphere, carrying out reduction reaction on SiO2 aerogel containing NiO and CoO to obtain the Ni-CoO / SiO2 aerogel. The Ni-CoO / SiO2 aerogel can realize hydrogen production through water photolysis of CoO, Ni promotes the hydrodeoxygenation process of guaiacol, meanwhile, the greenhouse effect of the porous structure of the SiO2 aerogel provides a high-temperature environment for the reaction process, the reaction is promoted to be continuously and positively carried out, and efficient conversion from guaiacol to phenol under the mild reaction condition is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a Ni-CoO / SiO 2 Aerogel and its preparation method and application. Background Art

[0002] In the aviation transportation industry, in order to further implement the emission reduction system and the dual carbon goals, the development of biofuels such as biojet fuel is the general trend. At present, the production of aviation biofuels by processing fats, oils and greases is a mature production route. However, at this stage, there is still a common problem of low energy density, and it is difficult to achieve the performance of 30% to 70% of cycloalkanes and aromatics required in modern aviation fuel on a large scale and stably, and it still needs to be mixed with 50% or more traditional fuels for use.

[0003] Lignin is the largest source of renewable aromatics in nature, and the bio-oil obtained from its hydrothermal liquefaction is considered to be one of the most effective ways to replace fossil fuels. However, bio-oil currently usually has a high oxygen content, resulting in severe corrosiveness and chemical instability. Therefore, it is necessary to improve the quality by hydrodeoxygenation. Due to the complexity and irregularity of lignin structure and its tendency to repolymerize, the conversion and utilization of lignin become relatively difficult. Therefore, current research is mostly based on screening catalysts for model compounds such as guaiacol, and studying the reaction mechanism of lignin hydrodeoxygenation. However, it is still a challenge to efficiently produce biofuels by low-temperature hydrodeoxygenation of guaiacol under hydrothermal conditions.

[0004] At present, the research on photothermal catalysis based on photothermal conversion has gradually received great attention from researchers in the field of energy and catalysis. Photothermal catalysis can not only reduce energy consumption and improve the reaction conditions of high temperature and high pressure, meet the requirements of environmental protection and sustainable development, but also effectively improve the reaction rate and product selectivity, and store solar energy in the form of chemical energy for utilization. However, achieving high temperature under unconcentrated sunlight is still a technical challenge. Traditional photocatalytic materials are based on semiconductors such as TiO 2 The utilization rate of solar energy is low. Only ultraviolet light and visible light can be used for photocatalytic reactions, while near-infrared (NIR) light, which accounts for nearly 54% of the sunlight spectrum, is not fully utilized. In addition, due to the disadvantages of easy recombination of photogenerated hole-electron pairs, the photocatalytic performance is greatly restricted. Therefore, it is crucial to develop photothermal catalysts with a wide absorption range, excellent photothermal conversion and adjustable selectivity to improve the energy conversion efficiency of solar energy to chemical energy for solar energy utilization and catalytic reactions.

[0005] In summary, developing a catalyst that can be used for the photothermal conversion of guaiacol to produce phenol is an important issue that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems existing in the prior art and provide a Ni-CoO / SiO 2 Aerogel and its preparation method and application.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a Ni-CoO / SiO 2 The method for preparing aerogel comprises the following steps:

[0009] (1) mixing water, tetraethyl orthosilicate, ethanol and hydrochloric acid solution, and hydrolyzing them to obtain silica sol;

[0010] (2) Mixing silica sol, nickel salt solution, cobalt salt solution and hydrochloric acid solution, and sequentially subjecting to ultrasonication, water bath and freeze drying to obtain SiO containing NiO and CoO 2 Aerogel;

[0011] (3) In a reducing atmosphere, SiO containing NiO and CoO 2 The aerogel is subjected to reduction reaction to obtain the Ni-CoO / SiO 2 Aerogel.

[0012] Preferably, in step (1), the molar ratio of water, tetraethyl orthosilicate and ethanol is 4-6:1-3:15-17;

[0013] The concentration of the hydrochloric acid solution is 0.8 to 1.2 mol / L, and the pH value of the solution obtained by mixing is 6 to 7.

[0014] Preferably, in step (2), the nickel salt solution is a nickel acetate tetrahydrate solution, and the cobalt salt solution is a cobalt acetate tetrahydrate solution;

[0015] The concentration of the nickel salt solution is 0.00018 to 0.00056 mol / mL, the concentration of the cobalt salt solution is 0.00038 to 0.00114 mol / mL, and the concentration of the hydrochloric acid solution is 0.8 to 1.2 mol / L.

[0016] Preferably, the volume ratio of the nickel salt solution in step (2), the cobalt salt solution in step (2) and the tetraethyl orthosilicate in step (1) is 20-25:10-15:40-50, and the pH value of the solution obtained by mixing is 7-8.

[0017] Preferably, in step (2), the ultrasonic temperature is 40 to 50° C., and the ultrasonic time is 0.5 to 1.5 h;

[0018] The temperature of the water bath is 50-70°C, and the time of the water bath is 15-45 minutes;

[0019] The freeze-drying temperature is -45 to -50°C, and the freeze-drying time is 40 to 56 hours.

[0020] Preferably, in step (3), the reducing atmosphere is a hydrogen atmosphere, and the flow rate of hydrogen is 80 to 100 mL / min.

[0021] Preferably, in step (3), the temperature of the reduction reaction is 400-420° C., and the time of the reduction reaction is 1.5-2.5 h.

[0022] The present invention also provides the Ni-CoO / SiO 2 Preparation method of aerogel Ni-CoO / SiO 2 Aerogel.

[0023] The present invention also provides the Ni-CoO / SiO 2 Application of aerogel in catalyzing photothermal conversion of guaiacol to produce phenol.

[0024] The beneficial effects of the present invention are:

[0025] The present invention provides a Ni-CoO / SiO 2 The preparation method of aerogel comprises the following steps: mixing water, tetraethyl orthosilicate, ethanol and hydrochloric acid solution, and performing hydrolysis to obtain silica sol; mixing silica sol, nickel salt solution, cobalt salt solution and hydrochloric acid solution, and sequentially performing ultrasonication, water bathing and freeze drying to obtain SiO containing NiO and CoO 2 Aerogel; SiO containing NiO and CoO under reducing atmosphere 2 Aerogel is reduced to obtain Ni-CoO / SiO 2 Aerogel. The preparation method of the present invention is simple and has low raw material cost. First, SiO containing NiO and CoO is prepared by a sol-gel method. 2 aerogel, and then Ni-CoO / SiO was prepared by hydrogen reduction treatment. 2 Aerogel, the active components in the aerogel catalyst are highly dispersed and have excellent photothermal catalytic performance. Ni-CoO / SiO 2 Aerogel catalysts can realize the photocatalytic hydrogen production from water by CoO, and Ni promotes the hydrogenation and deoxygenation of guaiacol. 2 The "greenhouse effect" of the porous structure of aerogel provides a high-temperature environment for the reaction process, promotes the continuous positive reaction, and realizes the efficient conversion of guaiacol to phenol under mild reaction conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The SiO2 containing NiO and CoO in Example 1 2SEM characterization and elemental line scan of aerogel; Figure 1 In the figure, a is SiO containing NiO and CoO. 2 SEM characterization of aerogel at 1 μm scale; b is SiO containing NiO and CoO 2 SEM characterization of aerogel at 200nm scale; c is SiO containing NiO and CoO 2 SEM characterization of aerogel at 100nm scale; d is SiO containing NiO and CoO 2 Si element line scan of aerogel; e is SiO containing NiO and CoO 2 Ni element line scan of aerogel; f is SiO containing NiO and CoO 2 Co element line scan of aerogel;

[0027] Figure 2 Schematic diagram of the programmed temperature reduction test results of different materials (Temperature—temperature, Intensity—strength);

[0028] Figure 3 is the Ni-CoO / SiO in Example 1 2 SEM characterization and EDS element mapping of aerogel; Figure 3 In the above equation, a is Ni-CoO / SiO 2 SEM characterization of aerogel at 10 μm scale; b is Ni-CoO / SiO 2 SEM characterization of aerogel at 2 μm scale; c is Ni-CoO / SiO 2 SEM characterization of aerogel at 1 μm scale; d is Ni-CoO / SiO 2 Si element distribution diagram of aerogel; e is Ni-CoO / SiO 2 Ni element distribution diagram of aerogel; f is Ni-CoO / SiO 2 Co element distribution map of aerogel. DETAILED DESCRIPTION

[0029] The present invention provides a Ni-CoO / SiO 2 The method for preparing aerogel comprises the following steps:

[0030] (1) mixing water, tetraethyl orthosilicate, ethanol and hydrochloric acid solution, and hydrolyzing them to obtain silica sol;

[0031] (2) Mixing silica sol, nickel salt solution, cobalt salt solution and hydrochloric acid solution, and sequentially subjecting to ultrasonication, water bath and freeze drying to obtain SiO containing NiO and CoO 2 Aerogel;

[0032] (3) In a reducing atmosphere, SiO containing NiO and CoO 2 The aerogel is subjected to reduction reaction to obtain the Ni-CoO / SiO 2 Aerogel.

[0033] In the present invention, in step (1), water, tetraethyl orthosilicate and ethanol are firstly mixed uniformly to obtain a first solution; then hydrochloric acid solution is slowly added dropwise to the first solution while stirring to hydrolyze tetraethyl orthosilicate to obtain silica sol.

[0034] In the present invention, in step (1), the molar ratio of water, tetraethyl orthosilicate and ethanol is preferably 4-6:1-3:15-17, more preferably 4.5-5.5:1.5-2.5:15.5-16.5, and more preferably 5:2:16.

[0035] In the present invention, in step (1), the concentration of the hydrochloric acid solution is preferably 0.8 to 1.2 mol / L, more preferably 0.9 to 1.1 mol / L, and more preferably 1.0 mol / L; the purpose of adding the hydrochloric acid solution in step (1) is to adjust the pH value, and the pH value of the solution obtained by mixing in step (1) is preferably 6 to 7, more preferably 6.2 to 6.8, and more preferably 6.5.

[0036] In the present invention, in step (2), the silica sol, the nickel salt solution and the cobalt salt solution are first mixed and stirred to obtain a second solution; then, the hydrochloric acid solution is slowly added dropwise to the second solution while stirring to obtain a composite sol; finally, the obtained composite sol is subjected to ultrasound, water bath and freeze drying in sequence to obtain a SiO2 containing NiO and CoO. 2 Aerogel.

[0037] In the present invention, in step (2), the nickel salt solution is preferably a nickel acetate tetrahydrate solution, and the cobalt salt solution is preferably a cobalt acetate tetrahydrate solution.

[0038] In the present invention, in step (2), the concentration of the nickel salt solution is preferably 0.00018 to 0.00056 mol / mL, more preferably 0.00028 to 0.00046 mol / mL, and more preferably 0.00037 mol / mL; the concentration of the cobalt salt solution is preferably 0.00038 to 0.00114 mol / mL, more preferably 0.00057 to 0.00095 mol / mL, and more preferably 0.00076 mol / mL; the concentration of the hydrochloric acid solution is preferably 0.8 to 1.2 mol / L, more preferably 0.9 to 1.1 mol / L, and more preferably 1.0 mol / L.

[0039] In the present invention, the volume ratio of the nickel salt solution in step (2), the cobalt salt solution in step (2) and the tetraethyl orthosilicate in step (1) is 20-25:10-15:40-50, more preferably 21-24:11-14:43-47, and more preferably 22:11:44.34; the purpose of adding the hydrochloric acid solution in step (2) is to adjust the pH value, and the pH value of the solution obtained by mixing in step (2) is preferably 7-8, more preferably 7.2-7.8, and more preferably 7.5.

[0040] In the present invention, in step (2), the temperature of ultrasound is preferably 40-50°C, more preferably 43-47°C, and more preferably 45°C; the time of ultrasound is preferably 0.5-1.5h, more preferably 0.7-1.3h, and more preferably 1h.

[0041] In the present invention, the temperature of the water bath is preferably 50 to 70° C., more preferably 55 to 65° C., and more preferably 60° C.; the time of the water bath is preferably 15 to 45 min, more preferably 20 to 40 min, and more preferably 30 min.

[0042] In the present invention, the freeze-drying temperature is preferably -45 to -50°C, more preferably -46 to -49°C, and more preferably -47 to -48°C; the freeze-drying time is preferably 40 to 56 h, more preferably 44 to 52 h, and more preferably 48 h.

[0043] In the present invention, in step (3), the reducing atmosphere is preferably a hydrogen atmosphere, and the flow rate of hydrogen is preferably 80 to 100 mL / min, more preferably 85 to 95 mL / min, and more preferably 90 mL / min.

[0044] In the present invention, in step (3), the temperature of the reduction reaction is preferably 400-420°C, more preferably 405-415°C, and more preferably 410°C; the time of the reduction reaction is preferably 1.5-2.5h, more preferably 1.7-2.3h, and more preferably 2h.

[0045] The present invention also provides the Ni-CoO / SiO 2 Preparation method of aerogel Ni-CoO / SiO 2 Aerogel.

[0046] In the present invention, Ni-CoO / SiO 2 In aerogel, Ni-CoO / SiO 2 SiO in aerogel 2 The mass fraction of the aerogel is 50-55%, the mass fraction of Ni is 20-25%, and the mass fraction of CoO is 22-27%.

[0047] The present invention also provides the Ni-CoO / SiO 2 Application of aerogel in catalyzing photothermal conversion of guaiacol to produce phenol.

[0048] In the present invention, the application comprises the following steps: in a photocatalytic reactor, Ni-CoO / SiO 2 Aerogel, guaiacol and water are mixed and reacted to prepare phenol; the Ni-CoO / SiO 2 The mass volume ratio of aerogel, guaiacol and water is preferably 0.2-0.4 g: 6 mL: 60 mL, more preferably 0.25-0.35 g: 6 mL: 60 mL, and more preferably 0.3 g: 6 mL: 60 mL; the optical power density of the reaction is preferably 350-450 mW / cm 2 , more preferably 370 to 430 mW / cm 2 , more preferably 400 mW / cm 2 The reaction temperature is preferably 200-250°C, more preferably 220-230°C, and more preferably 225°C.

[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0050] Example 1

[0051] Water, tetraethyl orthosilicate and ethanol were mixed evenly (the molar ratio of water, tetraethyl orthosilicate and ethanol was 5:2:16) to obtain a first solution; then a hydrochloric acid solution with a concentration of 1.0 mol / L was slowly added to the first solution (the pH value of the solution obtained after the addition was completed was 6.5), and the tetraethyl orthosilicate was hydrolyzed while being added and stirred to obtain silica sol; the silica sol, a nickel acetate tetrahydrate solution with a concentration of 0.00037 mol / mL and a cobalt acetate tetrahydrate solution with a concentration of 0.00076 mol / mL were mixed (the concentration of the hydrochloric acid solution was 1.0 mol / L) to obtain a first solution; then a hydrochloric acid solution with a concentration of 1.0 mol / L was slowly added to the first solution (the pH value of the solution obtained after the addition was completed was 6.5), and the hydrolysis of the tetraethyl orthosilicate was carried out while being added and stirred to obtain silica sol; The volume ratio of nickel tetrahydrate solution, cobalt acetate tetrahydrate solution and the above-mentioned ethyl orthosilicate is 22:11:44.34), and the mixture is stirred evenly to obtain a second solution; then, a hydrochloric acid solution with a concentration of 1.0 mol / L is slowly added to the second solution (the pH value of the solution obtained after the addition is 7.5), and the mixture is stirred while being added to obtain a composite sol; the obtained composite sol is ultrasonicated at 45°C for 1 hour, and then water-bathed at 60°C for 30 minutes, and finally freeze-dried at -48°C for 48 hours to obtain SiO containing NiO and CoO. 2 Aerogel;

[0052] SiO containing NiO and CoO was heated under hydrogen atmosphere. 2The aerogel was subjected to reduction reaction, the hydrogen flow rate was set to 90 mL / min, the reduction temperature was set to 410 °C, and the time was set to 2 h to obtain Ni-CoO / SiO 2 Aerogel.

[0053] The SiO containing NiO and CoO prepared in Example 1 2 The aerogel was characterized by scanning electron microscopy to obtain SiO containing NiO and CoO in Example 1. 2 SEM characterization and element line scan of aerogel, such as Figure 1 As shown; Figure 1 In the figure, a is SiO containing NiO and CoO. 2 SEM characterization of aerogel at 1 μm scale; b is SiO containing NiO and CoO 2 SEM characterization of aerogel at 200nm scale; c is SiO containing NiO and CoO 2 SEM characterization of aerogel at 100nm scale; d is SiO containing NiO and CoO 2 Si element line scan of aerogel; e is SiO containing NiO and CoO 2 Ni element line scan of aerogel; f is SiO containing NiO and CoO 2 Co element line scan of aerogel. Figure 1 It can be seen that SiO containing NiO and CoO 2 Aerogel has a bead-like porous structure, so its "greenhouse effect" provides a high-temperature environment for the reaction process, and it can be seen that Ni and Co are in the SiO 2 Evenly distributed in the aerogel.

[0054] Water, tetraethyl orthosilicate and ethanol were uniformly mixed (the molar ratio of water, tetraethyl orthosilicate and ethanol was 15:4:32) to obtain a first solution; then a hydrochloric acid solution with a concentration of 1.0 mol / L was slowly added to the first solution (the pH value of the solution obtained after the addition was completed was 5.5), and the solution was stirred while being added to hydrolyze the tetraethyl orthosilicate to obtain a silica sol; the obtained silica sol was ultrasonicated at 45°C for 1 hour, and then a 0.65 mol / L ammonia solution was slowly added thereto (the pH value of the solution obtained after the addition was completed was 6.5), and the solution was stirred while being added, and then the solution was water bathed at 60°C for 30 minutes, and finally, the solution was freeze-dried at -48°C for 48 hours to obtain SiO 2 Aerogel (labeled as SiO 2 ). The other conditions in Example 1 were kept unchanged, nickel acetate tetrahydrate solution was not added, and reduction reaction was not performed to prepare CoO / SiO 2 Aerogel (labeled as CoO / SiO 2). The other conditions in Example 1 were kept unchanged, the cobalt acetate tetrahydrate solution was not added, and the reduction reaction was not performed to prepare NiO / SiO 2 Aerogel (labeled as NiO / SiO 2 ). 2 、CoO / SiO 2 、NiO / SiO 2 、NiO-CoO / SiO 2 (SiO containing NiO and CoO prepared in Example 1 2 aerogel) were subjected to temperature programmed reduction tests to obtain schematic diagrams of temperature programmed reduction test results of different materials, as shown in Figure 2 As shown. Figure 2 It can be seen that NiO / SiO 2 The reduction peak of NiO appears at 355-470℃ in aerogel; the peak of CoO / SiO 2 The reduction peak of CoO appears at about 560-720℃ in aerogel; NiO-CoO / SiO 2 Aerogel at 280~450℃ and NiO / SiO 2 The surface redox peaks of the aerogels are similar to those of CoO / SiO 2 The surface redox peaks of the aerogels are similar, so the reduction at 410 °C can obtain Ni-CoO / SiO 2 Aerogel.

[0055] The Ni-CoO / SiO prepared in Example 1 2 The aerogel was characterized by scanning electron microscopy and EDS element mapping to obtain the Ni-CoO / SiO 2 SEM characterization and EDS element mapping of aerogel, such as Figure 3 As shown; Figure 3 In the above equation, a is Ni-CoO / SiO 2 SEM characterization of aerogel at 10 μm scale; b is Ni-CoO / SiO 2 SEM characterization of aerogel at 2 μm scale; c is Ni-CoO / SiO 2 SEM characterization of aerogel at 1 μm scale; d is Ni-CoO / SiO 2 Si element distribution diagram of aerogel; e is Ni-CoO / SiO 2 Ni element distribution diagram of aerogel; f is Ni-CoO / SiO 2 Co element distribution diagram of aerogel. Figure 3 It can be seen that the SiO containing NiO and CoO prepared in Example 1 2The aerogel still maintains a bead-chain-like porous structure after thermal hydrogenation, indicating that the thermal hydrogenation does not destroy the SiO 2 The morphology and structure of aerogel, Ni and Co in SiO 2 The SiO2 is also evenly distributed in the aerogel, and after thermal hydrogenation, 2 The distribution of Ni and Co elements in aerogel is more uniform.

[0056] Comparative Example 1

[0057] The other conditions in Example 1 were kept unchanged, and the molar ratio of water, tetraethyl orthosilicate and ethanol was changed to 15:4:32 to obtain Ni-CoO / SiO 2 Aerogel.

[0058] Comparative Example 2

[0059] The other conditions in Example 1 were kept unchanged, and the molar ratio of water, tetraethyl orthosilicate and ethanol was changed to 3:1:8 to obtain Ni-CoO / SiO 2 Aerogel.

[0060] Comparative Example 3

[0061] The other conditions in Example 1 were kept unchanged, and the molar ratio of water, tetraethyl orthosilicate and ethanol was changed to 9:4:32 to obtain Ni-CoO / SiO 2 Aerogel.

[0062] The Ni-CoO / SiO prepared in Example 1 and Comparative Examples 1 to 3 were 2 The density and specific surface area of ​​the aerogels were characterized to obtain different Ni-CoO / SiO 2 The properties of the aerogel are shown in Table 1.

[0063] Table 1 Different Ni-CoO / SiO 2 Aerogel properties

[0064] Case <![CDATA[Density (g / cm 3 )]]> <![CDATA[Specific surface area (g / m 2 )]]> Example 1 0.2973 575.26 Comparative Example 1 0.3076 100.40 Comparative Example 2 0.3040 53.07 Comparative Example 3 0.6318 494.32

[0065] As can be seen from Table 1, the Ni-CoO / SiO 2 Aerogel has the best properties, with a density of up to 0.2973g / cm 3 , the specific surface area can reach 575.26g / m 2 Therefore, due to the "greenhouse effect" of the porous structure, a high-temperature environment can be provided for the reaction process, resulting in a better catalytic effect.

[0066] Application Example 1

[0067] In a photocatalytic reactor, 0.3 g of the Ni-CoO / SiO prepared in Example 1 was added. 2 Aerogel, 6 mL of guaiacol and 60 mL of water were mixed and the light power density was 400 mW / cm 2 The hydrothermal reaction was carried out at a temperature of 225°C and the reaction time was set to 30 min. The selectivity of phenol in the product was tested.

[0068] Application Comparative Example 1

[0069] The other conditions in Example 1 remain unchanged, and the experiment is carried out without light, without adding the Ni-CoO / SiO prepared in Example 1. 2 Aerogel, testing the selectivity of phenol in the product.

[0070] Application Comparative Example 2

[0071] The other conditions in Example 1 remain unchanged, and the Ni-CoO / SiO prepared in Example 1 is not added. 2 Aerogel, testing the selectivity of phenol in the product.

[0072] Application Comparative Example 3

[0073] Water, tetraethyl orthosilicate and ethanol were uniformly mixed (the molar ratio of water, tetraethyl orthosilicate and ethanol was 15:4:32) to obtain a first solution; then a hydrochloric acid solution with a concentration of 1.0 mol / L was slowly added to the first solution (the pH value of the solution obtained after the addition was completed was 5.5), and the solution was stirred while being added to hydrolyze the tetraethyl orthosilicate to obtain a silica sol; the obtained silica sol was ultrasonicated at 45°C for 1 hour, and then a 0.65 mol / L ammonia solution was slowly added thereto (the pH value of the solution obtained after the addition was completed was 6.5), and the solution was stirred while being added, and then the solution was water bathed at 60°C for 30 minutes, and finally, the solution was freeze-dried at -48°C for 48 hours to obtain SiO 2 Aerogel (labeled as SiO 2 );

[0074] The other conditions in Application Example 1 remain unchanged, and the Ni-CoO / SiO 2 Aerogel replaced by SiO 2 , test the selectivity of phenol in the product.

[0075] Application Comparative Example 4

[0076] The other conditions in Example 1 were kept unchanged, nickel acetate tetrahydrate solution was not added, and reduction reaction was not performed to prepare CoO / SiO 2 Aerogel (labeled as CoO / SiO 2 );

[0077] The other conditions in Application Example 1 remain unchanged, and the Ni-CoO / SiO 2 Aerogel replaced by CoO / SiO 2 , test the selectivity of phenol in the product.

[0078] Application Comparative Example 5

[0079] Control the other conditions in Example 1 unchanged, without adding the cobalt acetate tetrahydrate solution, to prepare Ni / SiO 2 Aerogel (labeled as Ni / SiO 2 );

[0080] The other conditions in Application Example 1 remain unchanged, and the Ni-CoO / SiO 2 Aerogel replaced by Ni / SiO 2 , test the selectivity of phenol in the product.

[0081] The test results of phenol selectivity in the products of Application Example 1 and Comparative Application Examples 1 to 5 are recorded in Table 2.

[0082] Table 2 Test results of phenol selectivity in the products of Application Example 1 and Comparative Examples 1 to 5

[0083] Application Cases Phenol selectivity (%) Application Example 1 15.57 Application Comparative Example 1 3.76 Application Comparative Example 2 4.27 Application Comparative Example 3 12.84 Application Comparative Example 4 7.08 Application Comparative Example 5 4.62

[0084] It can be seen from Table 2 that at a temperature of 225°C, Ni-CoO / SiO 2 Aerogel at an optical power density of 400mW / cm 2 The selectivity of guaiacol to phenol by photothermal conversion can reach 15.57%, which is 11.81% higher than that under the conditions without light and aerogel catalyst and 11.30% higher than that under the conditions of light only. 2 Aerogel has good photothermal catalytic effect; at a light power density of 400mW / cm 2 , under the condition of temperature of 225℃, Ni-CoO / SiO 2 Aerogel can realize the one-pot method of CoO photolysis of water to produce hydrogen, Ni promotes the hydrogenation and deoxygenation of guaiacol, and SiO 2 The "greenhouse effect" of the porous structure of aerogel provides a high-temperature environment for the reaction process, promotes the continuous positive reaction, and realizes the efficient conversion of guaiacol to phenol under mild reaction conditions.

[0085] From the above embodiments, it can be seen that the present invention provides a Ni-CoO / SiO 2The preparation method of aerogel comprises the following steps: mixing water, tetraethyl orthosilicate, ethanol and hydrochloric acid solution, and performing hydrolysis to obtain silica sol; mixing silica sol, nickel salt solution, cobalt salt solution and hydrochloric acid solution, and sequentially performing ultrasonication, water bathing and freeze drying to obtain SiO containing NiO and CoO 2 Aerogel; SiO containing NiO and CoO under reducing atmosphere 2 Aerogel is reduced to obtain Ni-CoO / SiO 2 Aerogel. The preparation method of the present invention is simple and has low raw material cost. First, SiO containing NiO and CoO is prepared by a sol-gel method. 2 aerogel, and then Ni-CoO / SiO was prepared by hydrogen reduction treatment. 2 Aerogel, the active components in the aerogel catalyst are highly dispersed and have excellent photothermal catalytic performance. Ni-CoO / SiO 2 Aerogel catalysts can realize the photocatalytic hydrogen production from water by CoO, and Ni promotes the hydrogenation and deoxygenation of guaiacol. 2 The "greenhouse effect" of the porous structure of aerogel provides a high-temperature environment for the reaction process, promotes the continuous positive reaction, and realizes the efficient conversion of guaiacol to phenol under mild reaction conditions.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing Ni-CoO / SiO2 aerogel, characterized in that: It includes the following steps: (1) mixing water, tetraethyl orthosilicate, ethanol and hydrochloric acid solution, and hydrolyzing them to obtain silica sol; (2) mixing silica sol, nickel salt solution, cobalt salt solution and hydrochloric acid solution, and sequentially subjecting to ultrasonication, water bath and freeze drying to obtain SiO2 aerogel containing NiO and CoO; (3) Under a reducing atmosphere, the SiO2 aerogel containing NiO and CoO is subjected to a reduction reaction to obtain the Ni-CoO / SiO2 aerogel.

2. The method for preparing Ni-CoO / SiO2 aerogel according to claim 1, characterized in that: In step (1), the molar ratio of water, tetraethyl orthosilicate and ethanol is 4-6:1-3:15-17; The concentration of the hydrochloric acid solution is 0.8 to 1.2 mol / L, and the pH value of the solution obtained by mixing is 6 to 7.

3. The method for preparing Ni-CoO / SiO2 aerogel according to claim 1 or 2, characterized in that: In step (2), the nickel salt solution is a nickel acetate tetrahydrate solution, and the cobalt salt solution is a cobalt acetate tetrahydrate solution; The concentration of the nickel salt solution is 0.00018 to 0.00056 mol / mL, the concentration of the cobalt salt solution is 0.00038 to 0.00114 mol / mL, and the concentration of the hydrochloric acid solution is 0.8 to 1.2 mol / L.

4. The method for preparing Ni-CoO / SiO2 aerogel according to claim 3, characterized in that: The volume ratio of the nickel salt solution in step (2), the cobalt salt solution in step (2) and the tetraethyl orthosilicate in step (1) is 20-25:10-15:40-50, and the pH value of the solution obtained by mixing is 7-8.

5. The method for preparing Ni-CoO / SiO2 aerogel according to claim 4, characterized in that: In step (2), the ultrasonic temperature is 40 to 50° C., and the ultrasonic time is 0.5 to 1.5 h; The temperature of the water bath is 50-70°C, and the time of the water bath is 15-45 minutes; The freeze-drying temperature is -45 to -50°C, and the freeze-drying time is 40 to 56 hours.

6. The method for preparing Ni-CoO / SiO2 aerogel according to claim 5, characterized in that: In step (3), the reducing atmosphere is a hydrogen atmosphere, and the flow rate of hydrogen is 80 to 100 mL / min.

7. The method for preparing Ni-CoO / SiO2 aerogel according to claim 6, characterized in that: In step (3), the temperature of the reduction reaction is 400-420° C., and the time of the reduction reaction is 1.5-2.5 h.

8. Ni-CoO / SiO2 aerogel prepared by the method for preparing Ni-CoO / SiO2 aerogel according to any one of claims 1 to 7.

9. Use of the Ni-CoO / SiO2 aerogel according to claim 8 in catalyzing the photothermal conversion of guaiacol to produce phenol.

Citation Information

Cited By

  • Ni-molybdenum oxide / Nb2O5 nano composite catalyst as well as preparation method and application thereof

    CN120679551A